Metode MOORA Diterapkan untuk Menentukan Promosi Karyawan PTPN 4, dengan Analisis Keputusan Berbasis Kriteria Objektif - Ade Haikal; Al-Khowarizmi (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
The application of the MOORA (Multi-Objective Optimization on the basis of Ratio Analysis) method in employee promotion decisions at PTPN 4 aims to enhance efficiency and objectivity in decision-making. This method allows managers to evaluate employees based on multiple criteria simultaneously, such as performance, experience, contributions, and other relevant factors. By considering these various aspects, MOORA helps make promotion decisions more transparent and fair. One of the primary advantages of applying the MOORA method is its ability to reduce bias that may occur during the promotion process. Bias can arise from subjectivity or imbalance in employee assessments, which are often based on individual judgments or personal perceptions. By using MOORA, promotion decisions are based on more objective and measurable data, making the process more systematic and structured. The MOORA method can also increase employee motivation. A transparent promotion process based on clear criteria provides employees with a strong incentive to continuously improve their performance. When employees know that promotions are based on fair evaluation, they are more motivated to work harder. This, in turn, will increase overall productivity and performance at PTPN 4. The implementation of MOORA at PTPN 4 also provides advantages in better human resource management. With the MOORA-based decision support system, managers can easily identify employees who have the best potential for promotion. This process involves several steps, such as data normalization, determining criteria weights, and calculating final values that reflect overall employee performance. The end result is the selection of employees who meet the qualifications and have outstanding performance for promotion, supporting the sustainable development of the organization.